Appetite loss as a potential predictor of suicidal ideation and self-harm in adolescents: A school-based study. (1st April 2017) - Kitagawa, Yuko; Ando, Shuntaro; Yamasaki, Syudo; Foo, Jerome Clifford; Okazaki, Yuji; Shimodera, Shinji; Nishida, Atsushi; Togo, Fumiharu; Sasaki, Tsukasa
Abstract: Suicide is a leading cause of death in adolescents, but detection of its risk is often challenging. Many mental illnesses share the common symptom of appetite loss and it is also known that people who suffer from these illnesses are at greater risk of suicide. However, the relationship between appetite loss and suicide risk has yet to be examined. For adolescents in particular, questions about appetite loss may be easier to answer than sensitive questions regarding mental health. The present study aims to investigate the association of appetite loss with suicidal ideation and self-harm in adolescents. Rates of adolescents with suicidal ideation or self-harm associated with appetite-loss were examined in 18, 250 Japanese junior and senior high school students (aged 12–18) using a self-report questionnaire. Insomnia, a physical symptom which has previously been associated with suicide risk, was also controlled for in the analysis. Results showed that rates of adolescents with suicidal ideation or self-harm significantly increased according to the degree of self-reported appetite loss. Similar results were observed for insomnia. Odds ratios (ORs) for suicidal ideation and self-harm were 5.5 and 4.1 for adolescents with appetite loss compared to those without it, and the ORs were 5.5 and 3.5 for those with insomnia compared to those without it, respectively, adjusting for sex and age ( p  < 0.001). ORs remained statistically significant after adjusting for depression/anxiety (General Health Questionnaire-12 score). In conclusion, self-reported appetite loss was highly associated with suicidal ideation and self-harm in adolescents; adolescents reporting physical symptoms such as loss of appetite or insomnia should be given careful attention.